How family caregivers of cancer patients manage symptoms at home: a systematic review - Ullgren, Helena; Tsitsi, Theologia; Papastavrou, Evridiki; Charalambous, Andreas (My University, 2018)
Introduction Cancer affects not only the patient, but also the whole family, especially when a member of the family assumes the role of the family caregiver. This puts an additional emotional, social and financial strain on the family caregivers. Family caregivers of cancer patients are actively involved in the care provided at the home setting through various ways including practical tasks, symptom management and care coordination. The focus of preceding studies on family caregivers and symptom management was either on pain or the patients’ and family caregivers’ experience of symptom management and coping. The aim of this review was to provide evidence on how family caregivers manage symptoms and side effects at home, in adult cancer patients throughout the disease trajectory. Methods A systematic literature review was performed in PubMed, CINAHL, Web of Science and the Cochrane Central Register of Controlled Trials with a combination of keywords and MeSH terms for family caregivers, cancer, symptoms, side effects and management. Based on predetermined inclusion and exclusion criteria, a total of 1270 articles were screened and 20 studies were included in the analysis. A descriptive analysis was performed due to the heterogeneity of the findings. Results The results showed that only a limited number of studies (3/20) explored how and what family caregivers do in symptom management as a primary outcome. Family caregivers provided psychosocial support, such as supporting and motivating the patient and maintaining social engagement. Caregivers provided physical support such as with the administration of medicine and tube feeding. As an integral part of managing the symptoms, family caregivers actively monitored and assessed symptoms to timely recognize any treatment related side effects, assess the response to therapeutic interventions and recognize possible deterioration in physical status. Furthermore, family caregivers were often the decision maker – being alert, watching and waiting and decided when to act and when not to act. Conclusions Family caregivers are doing work similar to healthcare professionals, when managing symptoms and side effects at home in patients with cancer. Advanced tasks such as assessing, monitoring and deciding when and how to act are included in the daily routine of family caregivers.
Keywords: Family caregivers; Cancer; Symptom management; Systematic review